An Efficient Cyclic Di‐AMP Based Artificial Metalloribozyme for Enantioselective Diels–Alder Reactions. Issue 28 (10th June 2020) - Qi, Qianqian; Lv, Shuting; Hao, Min; Dong, Xingchen; Gu, Youkun; Wu, Peizhe; Zhang, Wenyue; Chen, Yashao; Wang, Changhao
Abstract : The diverse structures of nucleic acids as scaffolds have brought the significant advancement for DNA‐based enantioselective catalysis, yet RNA‐based enantioselective catalysis is lacking investigation. Herein, we report a small, natural RNA of cyclic di‐AMP (c‐di‐AMP) and Cu 2+ ions assemble into an artificial metalloribozyme (c‐di‐AMP· Cu 2+ ), that could effectively catalyze the enantioselective Diels–Alder reactions with up to 80 % ee . The enantioselective catalytic performance of c‐di‐AMP· Cu 2+ has been studied by thorough investigations of different metal cofactors, c‐di‐AMP/Cu 2+ molar ratios, additives, buffers and c‐di‐AMP analogues. In addition, the assembly of c‐di‐AMP· Cu 2+ gives rise to 300‐fold and 5‐fold rate acceleration compared to the uncatalyzed reaction and Cu 2+ ions, respectively. This work provides a simple and efficient strategy to construct the RNA‐based catalysts that would expand the current nucleic acids‐based catalysis and might hint the possible catalytic RNA in primordial chemistry. Abstract : A small cyclic RNA of c‐di‐AMP and Cu 2+ ions could assemble into an artificial metalloribozyme, that is able to catalyze the enantioselective Diels–Alder reactions with up to 80 % ee . The presence of c‐di‐AMP in the metalloribozyme not only achieves the chirality transfer but also gives rise to a significant rate enhancement.